Peran Dinas Lingkungan Hidup Kota Jambi dalam Penerapan Sanksi Administrasi Denda Berdasarkan Peraturan Daerah Nomor 8 Tahun 2013 Tentang Pengelolaan Sampah - Herma Yanti; Dedy Syaputra; Melly Susyandari (Universitas Batanghari Jambi, 2020)
Based on the Jambi City Regional Regulation Number 8 of 2013 concerning Waste Management, violations of the prohibition on waste disposal are subject to administrative sanctions as the main penalty. The amount of the fine is set at a high amount and is applied by the Jambi City Environment Agency (DLH). However, there are still many violations of the prohibition. This study aims to discuss how to regulate the amount of the fine and how the role of DLH Jambi City in implementing fines for violations that occur. The approach used is the sociological legal approach, and research data consists of primary data and secondary data. The role of DLH is measured by the ability of DLH to apply the amount of fines that have been determined, from the amount and time span of the application of fines and from the types of violations for which fines have been applied. From the research results, it is known that from the ability to apply the amount of fines, the role of DLH is not optimal because the amount of fines applied to violators is not all according to the stipulated provisions. The amount and time span of the application of fines are also not optimal because they are not yet comparable to the intensity of violations that can be seen every day, while the application of fines that are carried out does not always exist every month. From the types of violations that have been subject to fines are also not optimal because not all types of violations that have occurred can be seen the application of the fine sanctions.